Searches for high-frequency variations in the 8B solar neutrino flux at the sudbury neutrino observatory - Aharmim, B; Ahmed, SN; Anthony, A; Barros, N; Beier, E; Bellerive, A; Beltran, B; Bergevin, M; Biller, S; Boudjemline, K; Boulay, MG; Burritt, T; et al. (Institute of Physics Publishing, 2010)
We have performed three searches for high-frequency signals in the solar neutrino flux measured by the Sudbury Neutrino Observatory, motivated by the possibility that solar g-mode oscillations could affect the production or propagation of solar 8B neutrinos. The first search looked for any significant peak in the frequency range 1-144day-1, with a sensitivity to sinusoidal signals with amplitudes of 12% or greater. The second search focused on regions in which g-mode signals have been claimed by experiments aboard the Solar and Heliospheric Observatory satellite, and was sensitive to signals with amplitudes of 10% or greater. The third search looked for extra power across the entire frequency band. No statistically significant signal was detected in any of the three searches. © 2010. The American Astronomical Society.